Bending creep of corrugated fibreboard in cycling relative humidity : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Agricultural Engineering at Massey University - McKenzie, Andrew David (Massey University, 1999)
Packaging of fresh fruit for export is a major use for corrugated fibreboard manufactured in New Zealand. However the cold and humid conditions used to preserve fruit quality are particularly detrimental to the strength of corrugated packaging. The main objective of this study was to develop a method to measure the performance of corrugated fibreboard in high and cycling relative humidity environments. This method was then used to compare the performance of three corrugated fibre-boards 1 For commercial reasons these will be referred to as 'CB1', 'CB2'and 'CB3' The creep performance of corrugated fibreboard was measured by subjecting samples to four point bending stress under controlled cyclic relative humidity conditions using a computer controlled testing apparatus. A mathematical model by Urbanik (1995) and an empirical exponential model were reviewed before selecting a three term model developed by Pecht (1985) to describe the deflection of the corrugated board. Cyclic relative humidity accelerated the rate of creep compared to a static high humidity environment. The rate of creep in the machine direction was found to be considerably lower than that in the cross machine direction. It was also found that increasing the peak relative humidity from 80% to 90% RH dramatically changed the deflection response. This provides a solution to conflicting data in the literature on relative humidity cycling effects. Isochronous deflection curves were used to compare the creep performance of the corrugated fibreboard samples in an environment cycling between 50% and 90% RH. Corrugated fibreboard sample CB1 had a slightly lower creep stiffness than corrugated boards CB2 (p=0.0580, n=8) and CB3 (p=0.0398, n=8). However a greater number of tests would be required on a wider range of samples to conclusively determine if there were differences in board performance.
Keywords: Fiberboard